The Effect Of Working Capital On Profitability At The Sri Rasa Cracker Factory In Bengkulu City - Jerry Kurnia Illahi; Bahman Efendi; Kamelia Astuty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the Effect of Working Capital on Profitability at the Sri Rasa Crackers Factory in Bengkulu City in 2023-2024. The type of research used is quantitative. The data collection method is done by documentation. The data used in this study is secondary data by collecting the Financial Report of the Sri Rasa Crackers Factory in Bengkulu City in 2023-2024. The results of the study indicate that the three variables, namely inventory turnover, collection period, and accounts payable turnover, have a positive and significant effect on company profitability. Partially, inventory turnover obtained a t-test value of 3.631 (Sig. 0.002), collection period of 3.964 (Sig. 0.001), and accounts payable turnover of 3.645 (Sig. 0.002). Simultaneously, the F-test results of 170.926 with a significance level of 0.000 (<0.05) and a coefficient of determination (R²) of 0.962 indicate that 96.2% of the variation in profitability is explained by these three variables. The increase in working capital efficiency is reflected in the increase in Net Profit Margin from 5.51% in 2023 to 6.21% in 2024, confirming that efficient management of inventory, receivables, and payables can significantly increase the company's profitability.